The Role of Language and Learning Advisers in University Settings: Helping Students to Help Themselves - Briguglio, Carmela (Bozen-Bolzano University Press, 2009)
A very diverse student body (particularly linguistically and culturally) is the norm in Australian tertiary institutions with many international students having to study in English as a second language. This paper briefly examines the approaches and provisions that Australian universities are adopting to help international students develop English language for academic purposes. Academic Language and Learning (ALL) advisers, whose role is to facilitate student learning, carry out this role in a number of different ways in different universities. This paper discusses how this role is carried out within the Communication Skills Centre of the Curtin Business School,at the Curtin University of Technology in Western Australia. Staff at the Centre have, over a number of years, adapted their role to ensure that students become active learners and take maximum responsibility for their own development.Some of the principles that have guided our work include: a continued emphasis on student development, rather than remediation; services available to all students studying at all levels across the Curtin Business School; support which aims to demystify academic discourse; student taking responsibility for their own work; and three way learning (students learn from us and from each other, but we also learn from them). This paper then discusses the strategies, based on the above principles, which have been adopted by staff to help students develop the skills they require in English for academic purposes. It is argued that the very diversity which marks our classrooms needs to be fully explored and built upon in order to teach valuable intercultural communication skills for global/multinational settings and to enrich the tertiary learning experience for all students.